Covered nitrogen levels on the evaluation of maize genotypes in late seeding - Carvalho, Edmar Vinícius de; Afférri, Flávio Sérgio; Peluzio, Joênes Mucci; Leal, Tarcisio Castro Alves Barros; Souza, Clóvis Maurílio de; Naoe, Lucas Koshy (Scientia Agraria Paranaensis, 2017)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <span style="font-family: 'Helvetica',sans-serif; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The aim of this work was to evaluate 12-maize genotypes and the effect of four covered N levels (20, 80, 140 and 200 kg ha-1), in the late seeding conditions (01/15/2014 and 02/25/2014) at Gurupi, Tocantis State, Brazil. The experiments were conducted in the randomized blocks design with three repetitions and 12 treatments. The followed traits were evaluated: foliar chlorophyll content between the V6-V8 and VT-R1 stages, dry weight of plant, grain number per spike, grain weight, grain yield, harvest index and productivity efficiency. The statistical analyze was done in each seeding, and the N effect was studied by the regression (orthogonal polynomial). It was shown significant difference among the genotypes in the greater number of evaluated traits and the grain yield of variety VAR8 and double-cross HD12 was classified in the superior statistical group in the two seeding dates (in average of four levels of nitrogen). These genotypes had shown the highest values of productive efficiency (0.58 to 0.75), and they were the superior genotypes that can be used for decrease the interval between the productive potential and the grain yield. The traits less responsives for the covered N were: foliar chlorophyll content between the V6-V8 stages, grain weight and harvest index.<!--StartFragment--><!--EndFragment-->